2016
DOI: 10.1002/2015gc006120
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity distribution and locking depth along the Main Marmara Fault, Turkey

Abstract: The seismicity along the Main Marmara Fault (MMF) below the Marmara Sea is analyzed during the 2007-2012 period to provide insights on the recent evolution of this important regional seismic gap. High precision locations show that seismicity is strongly varying along strike and depth providing fine details of the fault behavior that are inaccessible from geodetic observations. The activity strongly clusters at the regions of transition between basins. The Central basin shows significant seismicity located belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 44 publications
8
87
0
Order By: Relevance
“…The recent seismicity (between 2007 and 2012) around the Marmara Sea has been described in detail in Schmittbuhl et al [2016]. The study was based on an extended regional network of 132 stations.…”
Section: Waveform Databasementioning
confidence: 99%
See 1 more Smart Citation
“…The recent seismicity (between 2007 and 2012) around the Marmara Sea has been described in detail in Schmittbuhl et al [2016]. The study was based on an extended regional network of 132 stations.…”
Section: Waveform Databasementioning
confidence: 99%
“…Recently, Schmittbuhl et al [2016] concluded from the high-resolution analysis of the recent seismicity that the western part of the fault, i.e., the Central Basin, was hosting a significant creeping zone. Recently, Schmittbuhl et al [2016] concluded from the high-resolution analysis of the recent seismicity that the western part of the fault, i.e., the Central Basin, was hosting a significant creeping zone.…”
Section: Introductionmentioning
confidence: 99%
“…If this slip deficit corresponds to a steady state behavior of the fault, it implies that the NAF is currently accumulating stress at the surface. Over the width of the network, this information could help constraining the locking depth (see supporting information Figure S9); however, the current resolution is still insufficient to discriminate between shallow or deep estimates based on GPS or seismicity data [e.g., Ergintav et al, 2014;Schmittbuhl et al, 2015].…”
Section: 1002/2016gl069600mentioning
confidence: 99%
“…In the central Marmara Sea, the 70 km long Istanbul-Silivri segment (ISS) of the NAF has had no significant seismic events since at least 1766 and perhaps as far back as 989 [Ambraseys, 2002]. The probability of rupture of NAF segments in the central part of the Marmara Sea is considered to be significant [Murru et al, 2016;Aochi and Ulrich, 2015;Parsons, 2004], and Schmittbuhl et al [2015] recently interpreted the low level of present-day seismicity along the ISS as the signature of a locked behavior. Although Bohnhoff et al [2016] suggest that the maximum expected earthquake in the Istanbul area would probably not exceed a magnitude 7.5, geomechanical models generally predict high strain accumulation along the ISS, sufficient to produce a magnitude 7+ event [Hergert and Heidbach, 2010;Pondard et al, 2007;Armijo et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…The NAF poses an important hazard for the large cities surrounding the Marmara Sea region, particularly the megalopolis of Istanbul. Indeed, the NAF is presently hosting a long unruptured segment below the Sea of Marmara (Schmittbuhl et al 2015). The Marmara Sea is located in a transition zone where the rightlateral strike-slip character of the NAF meets with the extensional character of Aegean (e.g., Smith et al 1995).…”
Section: Introductionmentioning
confidence: 99%